ANALISIS KEMAMPUAN PASSING BAWAH PADA PEMAIN BOLAVOLI PADA KLUB IVO MARBO KABUPATEN TAKALAR - Ishak Bachtiar; Jusran S (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2023)
The aims of this study was to determine the lower passing ability of volleyball players at the IVO Marbo club, Takalar Regency. The method used in this study is a descriptive method with a quantitative approach and data collection is carried out through a pairing test. The population in this study were all volleyball players for the IVO Marbo club, Takalar Regency and the samples taken in this study were 20 people with a total sampling technique. The data analysis technique used is descriptive statistics using computer facilities through the SPSS version 25.0 for Windows program. Based on the results of the data and discussion of this study, it can be concluded that the results of the lower passing ability test for volleyball players at the IVO Marbo club, Takalar Regency, can be categorized as very good with a percentage of 40%. Key wards: passing down